Effect of socioeconomic status on hepatocellular carcinoma incidence and stage at diagnosis, a population‐based cohort study. (27th October 2015) - Anyiwe, Kika; Qiao, Yao; De, Prithwish; Yoshida, Eric M.; Earle, Craig C.; Thein, Hla‐Hla
Abstract: Background & Aims: Hepatocellular carcinoma (HCC) incidence is increasing worldwide and cirrhosis is the most important risk factor predominantly caused by chronic viral hepatitis infection. We studied the impact of socioeconomic status (SES) on HCC incidence and stage at diagnosis among viral hepatitis cases. Methods: A population‐based retrospective cohort study was conducted through the Ontario Cancer Registry linked data. Incidence rates were calculated using person‐time methodology. Association between SES (income quintile) and HCC incidence was assessed using proportional‐hazards regression. The impact of SES on HCC stage was investigated using logistic regression. Results: Among 11 350 individuals diagnosed with viral hepatitis between 1991 and 2010, a crude HCC incidence rate of 21.4 cases per 1000 person‐years was observed. Adjusting for age, gender, urban/rural residence and year of viral hepatitis diagnosis, a significant association was found between SES and HCC incidence, with an increased risk among individuals in the lowest three income quintiles (incidence rate ratio, IRR = 1.235; 95% CI: 1.074–1.420; IRR = 1.183; 95% CI: 1.026–1.364; IRR = 1.158; 95% CI: 1.000–1.340 respectively). No significant association between SES and HCC incidence was found after additionally adjusting for risk factors associated with HCC. However, HCC risk factors such as cirrhosis and HIV are associated with SES. Furthermore, no association was found between SES and HCC stage. Conclusions: The association between SES and HCC incidence is likely because of differences in risk factors across income quintiles. Investigating how SES affects HCC incidence facilitates an understanding of which populations are at elevated risk for HCC.